2018
DOI: 10.1177/0022429418784563
|View full text |Cite
|
Sign up to set email alerts
|

Achievement Goals, Implicit Theories, and Intrinsic Motivation: A Test of Domain Specificity Across Music, Visual Art, and Sports

Abstract: The purpose of this study was to test the domain specificity of achievement goals across music, visual art, and sports specializations, as measured by Elliot’s 2 × 2 achievement goal framework. Participants in the study were 103 volunteer student teachers from a teacher training institute in Singapore specializing in music, visual art, and physical education. Data were collected via self-report questionnaires that included measures of (a) the 2 × 2 achievement goal orientation constructs; (b) incremental and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 40 publications
(76 reference statements)
0
15
0
7
Order By: Relevance
“…On the other hand, when a competitive climate is desired, intrateam rivalry and environments oriented toward performance will be promoted [ 24 ]. As a result, athletes will adopt a motivational climate associated with either intrinsic or extrinsic motivations [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, when a competitive climate is desired, intrateam rivalry and environments oriented toward performance will be promoted [ 24 ]. As a result, athletes will adopt a motivational climate associated with either intrinsic or extrinsic motivations [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Correctly executed exercise could be rewarded with a simpler auditory feedback such as a click [215], or by a movement sonication such as experimented in physical rehabiliation [579,711], or with music feedback that was shown recently to improve deadlift technique [499]. In sEMG studies, it was shown tha tfocused verbal feedback had a positive impact on activating triceps brachii more than without feedback [249,604], highlighting the need of some human oversight and encouragement [565,852].…”
Section: B Real-time Feedback Methodsmentioning
confidence: 99%
“…More specifically, United States and Singapore nonmusic majors similarly reported higher levels of achievement goals toward their university major academic field than band. Wang et al (2018) further ascertained the domain specificity of achievement goals using a sample of 103 music, visual art, and sports student teachers from Singapore and found that participants rated achievement goals the highest in their own area of specialization. Furthermore, mastery-approach goals were associated with enjoyment in each of the three domains.…”
Section: Music and Other Domainsmentioning
confidence: 99%
“…While mastery-approach goals (e.g., “It is important to me to perform as well as I possibly can”) center on improving oneself, acquiring skills, and mastering tasks, mastery-avoidance goals (e.g., “I worry that I may not perform as well as I possibly can”) focus on avoiding not finishing a task or not being able to learn. In like vein, while performance-approach goals (e.g., “It is important to me to do well as compared to others”) emphasize learning for the sake of winning or doing better than others, performance-avoidance goals (e.g., “I just want to avoid performing worse that others”) stress avoiding doing worse than others or losing (Wang, Tan, & Dairianathan, 2018, p. 326). It is crucial to emphasize that learners can simultaneously espouse each of the four goals to varying degrees; they are by no means mutually exclusive (Pintrich & Garcia, 1991).…”
mentioning
confidence: 99%